Venice in Poetry and Prose: Adam Wiedemann’s Visit to the City - Czyżak, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The main aim of the article is to identify key interpretation issues in two texts by Adam Wiedemann. Both texts feature contemporary literary pictures of visits to Venice – the Polish author wrote a short story (Sens życia. Opowiadanie śródziemnomorskie, 1998) and a poem (Tramwaj na Lido, 2015) about his journeys to Italy. Those textual visions of the urban space of Venice show that Wiedemann is fully aware of many similar attempts made earlier yet still strives to stress his distinctness, creating a record of meetings of the contemporary visitor with the unique phenomenon of the unusual urban phenomenon.